Representation of solution for a linear fractional delay differential equation of Hadamard type - Peng Yang; JinRong Wang; Yong Zhou (Advances in Difference Equations, 2019)
Abstract This paper is devoted to seeking the representation of solutions to a linear fractional delay differential equation of Hadamard type. By introducing the Mittag-Leffler delay matrix functions with logarithmic functions and analyzing their properties, we derive the representation of solutions via the constant variation method.